Innovative methods of technical and vocational education: report - Kronner, Hans ed. (Federal Ministry of Education and Science BonnDE, 1989)
The topic was first considered on the macro level and different models such as company and school cooperatives were examined along with case studies from Japan, Sweden, Germany and Brazil. At the micro level, didactic models such as the concept of modules of employable skills (MES) training; on-the-job learning; project instruction; course instruction; and learning in school-run enterprises were looked at in conjunction wuth case studies from I.L.O., Nigeria, Egypt, Federal Republic of Germany, France, China and Singapore.